Self-assembled hybrid precursors towards more efficient propane ODH NiMoO4 catalysts. Issue 15 (11th May 2016) - Farin, B.; Eloy, P.; Poleunis, C.; Devillers, M.; Gaigneaux, E. M.
Abstract : This work shows a novel method to synthesize bulk NiMoO4 from hybrid materials made of guest ions (Ni and Mo precursors) and a polyampholytic comb-like copolymer displaying a supramolecular organization. Abstract : This work shows a novel method to synthesize bulk NiMoO4 from hybrid materials made of guest ions (Ni and Mo precursors) and a polyampholytic comb-like copolymer displaying a supramolecular organization. This supramolecular organization is crucial because the copolymer serves as a nanostructuring template. While non-porous α-NiMoO4 is obtained with classical methods, mesoporous β-NiMoO4 is prepared here. The β-phase is more efficient in the oxidative dehydrogenation of propane (ODHP). Our strategy assumed that the properties of a catalyst strongly depend on the features of the precursor from which it comes. This is why the precursors were meticulously characterized. Homogeneous hybrids were successfully synthesized where MoO4 2− anions establish electrostatic interactions with the copolymer's positive charges. The nickel cations are stabilized inside the matrix thanks to their coordination by the copolymer COO − functions. By bridging two copolymers, such coordination bonds reinforce the copolymer organization and enable to generate the organized hybrids. Some hybrids were then calcined, characterized and tested in the ODHP reaction. Preparing the β-phase generally requires temperatures beyond 600 °C which favours sintering and makes NiMoO4 poorly active. The use of supramolecularly organized precursors and the possibility it offers to form oxides under "soft conditions" lead to mesoporous β-NiMoO4 . The most propene selective β-NiMoO4 is generated here without sacrificing its specific surface area, maintaining its remarkably high activity level. This enables reaching higher propene yields than usual.